Genetic syndromes associated with ocular anomalies - Hartono Hartono (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1987)
A syndrome is defined as the concurrence or running together of constant patterns of abnormal signs or symptoms. Syndromes can be either genetic or non-genetic in origins. Genetic diseases consist of genic diseases, chromosomic diseases and embryopathies. Genetic syndromes also consist of genic disease syndromes, chromosomic disease syndromes and embryopathic syndromes. Syndromes of genic diseases are caused by pleiotropic mutation of the genes which give rise to multiple (pleiotropic) effects. Syndromes of chromosomic diseases are caused by chromosomal derangement either by the abnormalities of their structure or their number. There are many genetic syndromes associated with ocular anomalies. Geeraets has collected 436 ocular syndromes either genetic and non-genetic in origins, and 49 of 135 recognizable human malformations collected by Smith are also associated with ocular defects. Some important chromosomic syndromes such as tkisomy 21, Patau, Edward, and cri-du-chat syndromes are also associated with ocular anomalies. Key Words: genetic diseases - pleiotropic effects - ocular anomalies - chromosomic syndromes - embryopathies